Partial disability system and labor market adjustment: The case of Spain - Jose I. Silva; Judit Vall-Castello (W.E. Upjohn Institute for Employment Research, 2013)
Although partially disabled individuals in Spain are allowed to combine the receipt of disability benefits with a job, the empirical evidence shows that employment rates for this group of individuals are very low. Therefore, in this paper we construct labor market model with search intensity and matching frictions in order to identify the incentives and disincentives to work provided by the partial disability system in Spain from the point of view of both disabled individuals and employers. According to the model, the high employment rate gap observed between nondisabled and disabled workers can be partially explained by the presence of a lower level of productivity and higher searching costs among disabled individuals that discourage them from looking for jobs. Moreover, the design of the Spanish Disability System also contributes in explaining this gap. We also analyze the role of business cycle conditions in shaping the labor market transitions of disabled individuals.
Keywords: I18; J64; J68; 330; disability system; job search intensity; flow analysis.